Effect Of Credit Risk, Liquidity Risk, And Operational Risk On Profitability (Study On Banco Nasional De Comércio De Timor-Leste Bnctl-Dili) - Julmira Maria Lordes Cofitalan (ABM: International Journal of Administration, Business and Management, 2022)
The research aims to determine the effect of credit risk, liquidity risk, and operational risk on profitability on Banco Nasional do Comércio de Timor-Leste (BNCTL). The method used is quantitative descriptive analysis. This type of data is secondary data sourced from bank BNCTL's financial statements for the period 2010-2018, consisting of balance sheet statements and loss / profit statements. In this study, researchers conducted observations on financial statemens data through annual reports provided by BNCTL for the period 2010-2018, thus getting 9 years of observation. After secondary data is collected and analyzed it tested using multiple linear regression analysis models. This analysis model consists of a normality test, an autocorrelation test, a multicollinearity test, and a regression model determination test. Based on the results of the analysis found that Credit Risk has no significant effect on profitability (ROA), Liquidity Risk has an effect on credit risk.